Development Plans, Economic Indicators and Planning Challenges in Iran (1979-2022) - Seyed Hossein Mirjalili (International Journal Of Business and Development Studies, 2022)
In the decade of 1979-1988, there was no development plan in Iran. During 1989-2022, six development plans implemented in Iran's economy. The assessment of development plans conducted based on the performance and the results of economic indicators over the period. Economic Growth over the course of development plans was volatile. There has been a double-digit inflation rate over the course of the development plans and Productivity and the distribution of income indices were volatile. The challenges of planning in Iran include lack of common understanding on basic concepts of development plans, challenges of comprehensive plan, essential change due to external shocks, time span, parallel initiatives, coordination failure and lack of independent evaluation entity.
Keywords: 330; Development planning; Iran's Economy; Economic indicator; Diagnostics.; Iran's Economy; Economic indicator; Diagnostics